Perceived Effectiveness of Health Services offered by different Dairy Service Delivery Systems in Namakkal District of Tamil Nadu - Shanmugam, Karthikeyan; M C, Arunmozhi Devi; N, Narmatha; V, Uma; D, Thirunavukkarasu (Indian Journal of Dairy Science, 2018)
The present study was undertaken to understand the perceived effectiveness of health services offered by different dairy service providers in Namakkal district of Tamilnadu with respect to their regularity, timeliness, quality and cost. A total of 120 respondents who were availing the health services from different dairy service delivery systems were selected using proportionate random sampling and data were collected and analyzed. Most of the respondents predominantly availed the curative (99.17 per cent) and preventive (95.00 per cent) services from the private veterinarians; and medicines from the pharmacies (98.33 per cent) than other dairy service delivery systems. It was perceived by the dairy farmers that the curative services, preventive services and supply of medicines by private veterinarians were effective in terms of regularity (299.16, 299.12 and 299.15) and quality (299.16, 299.12 and 299.15). Dairy farmers perceived that public department provided cost effective curative services, preventive services and medicines (300 each) because most of the services were provided at free of cost. Further, they perceived that the timely curative (296.43) and preventive (273.75) services were provided by public department, whereas pharmacies delivered medicines (298.31) in time as they operate within the vicinity of the dairy farmers. Overall, the health services offered by the public departments were perceived to be most effective than other dairy service delivery systems.